Case report: Multimodal neoadjuvant and adjuvant chemotherapy for hepatic undifferentiated embryonal sarcoma in a young adult - Vergara, Rosemary; Khalil, Sarah; Munene, Gitonga (Frontiers in Oncology, 2022)
Hepatic undifferentiated embryonal sarcoma of the liver (UESL) is a rare hepatic malignancy found more commonly in pediatric patients. It has been associated with poor outcomes in adults and the role and timing of systemic therapy is unclear. There have been very few case reports detailing combination neoadjuvant and adjuvant chemotherapy use for hepatic undifferentiated embryonal sarcoma in adults. In this report, a 22-year-old male admitted with right upper quadrant pain was diagnosed with a 20 x 10 x 10 cm well-circumscribed, highly vascularized hepatic mass in the entirety of the left lobe. Biopsy confirmed the diagnosis of UESL. PET/CT showed no evidence of metastatic disease, and he received four cycles of Doxorubicin and Ifosfamide with demonstrated reduction in size and decrease in PET avidity. He underwent left hepatectomy with periportal lymphadenectomy, cholecystectomy, and partial gastrectomy with negative margins and received adjuvant Doxorubicin, Ifosfamide and Mesna. At 48 months, the patient was alive without evidence of disease. We hereby emphasize the potential advantages of combination chemotherapy and surgical resection in the management of UESL in adults.